Talent Management Implementation at an Open Distance E-Learning Higher Educational Institution: The Views of Senior Line Managers - Erasmus, Barney; Naidoo, Lynette; Joubert, Pierre (International Review of Research in Open and Distributed Learning, 2017)
The war for talent remains a challenge that many organisations face but more so for distance education institutions to deliver on its mandate to provide effective online academic offerings. The question that remains is: How can intellectual capital be managed effectively in order to recruit and retain talent that is necessary for success? This study was conducted at a mega open and distance learning institution, and this institution has identified talent management as one of the key strategic initiatives to ensure institutional strategic goal attainment and adopted an inclusive/developable talent approach as its framework. The aim of this article is to report on the perceptions of senior line managers regarding their experience with implementing the talent management strategy in their operational areas at the institution. This study adopted a qualitative approach and purposive sampling was used to select interviewees. The population group included chairpersons of 26 talent committees who are senior line managers and 11 of them were interviewed. Participants were of the opinion that policies and strategies do not always support the implementation of talent management in their respective environments. The findings show that although the university embraces the inclusive/developable talent approach in its strategy, the impact thereof is inhibited by a lack of methodological implementation, a lack of integration of supporting Human Resources policies with talent management, and insular line manager discernment.